Kebijakan Pengelolaan Dana Desa di Kabupaten Melawi, Kalimantan Barat - Ahirul Habib Padilah; Ira Patriani; Eka Apriyani; Dadi Sunarya Usfa Yursa; Ritaudin Ritaudin (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
This study examines the challenges faced in implementing village fund policies in Melawi Regency, which are not functioning effectively. The research aims to explore various aspects related to the policy implementation process, including socialization, resources, disposition, and bureaucracy. Empirical analysis is used to gain knowledge and understanding and to discover new concepts. The study finds that the implementation of village fund policies in Melawi Regency has been hindered by excessive verification workloads, delays in budget disbursement, actor capacity constraints in implementing policy SOPs, and planning of village policy programs that do not consider real data on community problems.